Clinical Analysis of Acinic Cell Carcinoma in Parotid Gland - Cha, Wonjae (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2011)
OBJECTIVES: Acinic cell carcinoma (AciCC) is a rarely encountered malignancy in parotid gland. Because AciCC is rare and was recently recognized as the entity of malignancy, AciCC has been difficult to study. We aimed to analyze the diagnosis and treatment experience for this malignancy in our hospital. METHODS: We retrospectively reviewed medical records of the 20 patients with AciCC of parotid gland diagnosed from 1990 to 2009. The preoperative computed tomography scan, preoperative fine needle aspiration cytology (FNAC) and intraoperative frozen section results were compared with the final diagnosis. The survival and recurrence were analyzed with the cancer stages and treatment modalities. RESULTS: There were 10 males and 10 females, with a mean age of 44.4 years, ranging 8-77 years. The AJCC tumor stage distributions of the patients were 70%, 15%, and 15% for stages I, II, and IV, respectively. The sensitivity of FNAC and intraoperative frozen section was 26.7% and 50.0% respectively. The 10-year survival rate was 90.9% with a mean follow-up of 111 months, ranging 17-251 months. The 10-year disease free survival rate was 74.2% and the mean duration of recurrence from initial surgery was 92.3 months. CONCLUSION: AciCC of the parotid gland is a rare malignancy that has features of less aggressive behavior, and good prognosis. Intraoperative frozen section examination may be helpful in the diagnosis of AciCC of the parotid gland because of the low sensitivity of preoperative computed tomography scan and FNAC. Surgery with adjuvant postoperative radiotherapy is satisfactory for disease control.